Towards a qualitative framework for blending equity and excellence in transforming South African higher education to achieve development - January, Chanaaz Charmain (School of Education, 2022)
South Africa has been on a difficult journey over the last two decades in its attempts to transform its higher education system. The key question around which major debates have revolved relates to achieving development within the context of a post-apartheid South Africa. At the heart of this question stand the twin imperatives of equity and excellence. This potential trade-off features extensively in the early theoretical work of Wolpe and Badat and is reflected in subsequent frameworks and policies. If the country had favoured excellence, as it was defined globally, the system's elite features would have been reproduced. Instead, South Africa aspired towards both excellence and equity. This choice has been critical, but it has not been easy for institutions to develop their own management strategies. Here, two critical global theories used to explain the drivers for human development, known as the human capital and human capability theories, were used to frame the research question. This study made use of these theoretical perspectives to understand the South African approach to the role of higher education in society. The political, social, economic, and ideological dimensions of development were thus deconstructed. With this background, the concepts of excellence and equity were further explored in relation to the higher education system's experience of massification and differentiation. Terms such as “quality”, “fitness for purpose”, “social justice”, and “equality” are relevant to this discussion and provide meaning for the concepts of excellence and equity. A grounded theory approach was used to gather data and sixteen leading experts in the field were participants representing an elite sample. These data provided the basis for the themes used to construct a qualitative framework for higher education transformation that reconciles both equity and excellence. This study led to the conclusion that transformation is founded on five key measurable indicators: individual transformation, student success, institutional culture, demographic representivity of staff and students, and defining and operationalising the South African knowledge project. The framework provides suggestions for understanding the project of higher education transformation and realising it through an ongoing process of consultation, action, and reflection.